Characteristics of the Central Nervous System Malformations Presented in Trisomy 13: A single-center Experience in Recognizing the Phenotype and Genotype - Faried, Ahmad; Laksono, Bremmy; Halim, Danny; Parikrama, Riksa; Sobana, Mirna; Arifin, Muhammad Zafrullah (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Patients who are diagnosed with trisomy 13 (Patau syndrome) are known to have a poor prognosis. It has been hypothesized that such poor outcomes are suspected to be attributed to their central nervous system (CNS)-malformations and cardiac-malformations. This study was conducted at Division of Neuropediatric, Department of Neurosurgery, Faculty of Medicine, Universitas Padjadjaran – Dr. Hasan Sadikin Hospital, Bandung (2012–2018). AIM: This study aimed to describe clinical characteristics and karyotype findings in patients who were diagnosed with Patau syndrome and treated at our center. Since Indonesia is still categorized as a lower middle-income country with limited resources, we expected that this study would provide a clinical reference on how a congenital disease with chromosomal abnormalities is confirmed. CASE PRESENTATION: Our cases indicate that CNS malformations are likely to be the cause of indirect mortality of patients’ early period of life. The median survival in our study is 7 days, while the longest survival is 30 days. The major cause of death is apnea, which found in 4 of 5 diagnosed infants. One patient died of severe infection. In most cases, where CNS malformations were observed microcephaly with sloping forehead, Dandy–Walker syndrome, lobar or alobar holoprosencephaly and ventriculomegaly were identified, as well as neural tube defects (NTDs) were identified, such as spina bifida and meningoencephalocele. CNS malformations, such as holoprosencephaly, may be associated with episodes characterized by temporary cessation of spontaneous breathing (apnea) as direct cause of mortality. CONCLUSION: We conclude that early treatment in Patau syndrome patient in our center should be focused on more life-threatening problem caused by CNS malformations than NTDs defects, such defects could be managed electively.